Effect of Motor Relearning Programme Combined with Jin's Three-Needle Therapy on Lower Limb Motor Function in Patients with Ischemic Stroke - Pincao GAO; Fang TANG; Weirong XIONG; Li YANG; Quan ZENG (康复学报)
Objective:To investigate the influence of motor relearning programme combined with Jin's three-needle therapy on lower limb motor function in patients with ischemic stroke.Methods:A total of 58 ischemic stroke patients were randomly divided into control group (n=28) and treatment group (n=30). Patients in the control group were treated with conventional rehabilitation training and Jin's three-needle therapy, while patients in the treatment group were treated with motor relearning programme on the basis of rehabilitation in the control group. The effects of rehabilitation, National Institutes of Health Stroke Scale (NIHSS), Fugl-Meyer Activity (FMA) (lower limb part), Barthel index (BI), maximum walking speed of 10 meters of the two groups were compared and statistically analyzed.Results:The effects of rehabilitation, such as NIHSS, FMA(lower limb part), BI, maximum walking speed of 10 meters of the treatment group were higher than before treatment (P< 0.05). The difference value of NIHSS scores in the treatment group decreased lower than that in the control group (P< 0.05). The difference value of FMA scores (lower extremity part), maximum walking speed of 10 meters, and BI scores of the treatment group increased more than those of the control group (P< 0.05), and the difference was statistically significant respectively (P< 0.05).Conclusion:Motor relearning programme combined with Jin's three-needle therapy can be effective in improving low limb motor function, daily living ability and quality of life of patients with ischemic stroke.